The Late Hellenistic military ship of Phanagoria: New data for the reconstruction of the ship - Poveda, Pierre; Boetto, Giulia; Olkhovskiy, Sergey V. (Sailing through History. Reading the Past – Imagining the Future: Proceedings of the 16th International Symposium on Boat & Ship Archaeology ISBSA 16, 2024)
The ship of Phanagoria was discovered in 2012 during the exploration of the port structures of the ancient city. The remains are nearly 16 m long and 2.7 m wide and preserved up to the caprail on port side. In 2014, a bronze casing decorated with a crescent and a five-rayed star was found 1.5 m to the west of the bow end. This bronze casing and the slender shape of the vessel have provided arguments to identify it with a military unit associated to Mithridates VI Eupator. This article presents the process carried out recently to reconstruct the original shape of the ship of Phanagoria, and discuss the results.